1978
DOI: 10.3386/w0248
|View full text |Cite
|
Sign up to set email alerts
|

Unionism and the Dispersion of Wages

Abstract: This study examines the effect of trade unionism on the dispersion of wages among male wage and salary workers in the private sector in the United States. It finds that the application of union wage policies designed to standardize rates within and across establishments significantly reduces wage dispersion among workers covered by union contracts and that unions further reduce wage dispersion by narrowing the white-collar/blue-collar differential within establishments. These effects dominate the more widely s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
47
0

Year Published

1981
1981
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 0 publications
7
47
0
Order By: Relevance
“…The empirical evidence for developed countries supports this proposition (Freeman, 1980;Blanchflower and Freeman, 1992;Bratsberg and Ragan, 1997). Table 3 presents the regression coefficients from the estimated union and nonunion wage equations (with and without industry dummies).…”
Section: Unions and Wage Dispersionmentioning
confidence: 55%
See 1 more Smart Citation
“…The empirical evidence for developed countries supports this proposition (Freeman, 1980;Blanchflower and Freeman, 1992;Bratsberg and Ragan, 1997). Table 3 presents the regression coefficients from the estimated union and nonunion wage equations (with and without industry dummies).…”
Section: Unions and Wage Dispersionmentioning
confidence: 55%
“…To test this proposition, I follow Freeman (1980) and decompose the variance of union wages into its explained and residual components: (2) and (3) and re-arranging, we obtain:…”
Section: Wage Dispersion and Dispersion Of Characteristics The Dispementioning
confidence: 99%
“…However, empirical evidence to date is mixed. Freeman (1980), Hirsch (1982), Belman and Heywood (1990), and Lemieux (1998) show that unions reduce wage dispersion, while Spetz et al (2011) find little evidence that unions have an effect on the wage structure of nurses. Furthermore, the literature does not discuss the effect of unions on the relative value of foreign education.…”
Section: Imperfect Competition In the Labor Marketmentioning
confidence: 92%
“…1 Unions can affect the distribution of earnings in several conflicting ways (Freeman, 1980(Freeman, , 1993Freeman and Medoff, 1984). 2 However, most empirical work has found that unions have generally reduced inequality (McCabe, 1912;Reynolds and Taft, 1959;Slichter et al, 1960;Hyclak, 1979;Freeman, 1980Freeman, , 1982Pfeffer and Ross, 1981;Hirsch, 1982;Freeman and Medoff, 1984;Quan, 1984). It thus is sensible to examine how the substantial decline in private-sector union density since the mid-1970s contributed to the overall inequality increase.…”
Section: Introductionmentioning
confidence: 98%